The probative value of the opinions of the parties' technical assistants in social security proceedings: an evaluative approach (Revista do Tribunal Regional Federal da 3ª Região, 2021)
The premise of this study is the importance of expert evidence in the social security procedural relationship in the Federal Court as a means of demonstrating the social rights of the beneficiaries. At the same time as looking at the probative value of the expert report prepared by the court's expert, it seeks to reinforce the need to value the opinion of the parties' technical assistant. The expected contribution of this approach is the construction of a collaborative procedural relationship between the parties, valuing the dialogue between the technical professionals who seek to shed light on the issues submitted to the magistrate.
Keywords: social security process; opinion; technical assistant; probative value; expert evidence; valuing dialogue